PKCδ stabilizes TAp63 to promote cell apoptosis. Issue 16 (23rd June 2015) - Li, Decai; Li, Chenghua; Wu, Min; Chen, Qiongqiong; Wang, Qiao; Ren, Jian; Zhang, Yujun
Abstract : PKCδ and p63 are respectively reported to play important roles in cell apoptosis. But there is no report on interaction between them in regulation of apoptosis. In the present study, we found that PKCδ can directly associate and up‐regulate TA isoforms of p63 (TAp63) proteins via increasing their stability. PKCδ kinase activity and Thr157 site in TAp63 are crucial for this PKCδ‐induced accumulation of TAp63. PKCδ can also enhance TAp63‐mediated transcription and cell apoptosis. Taken together, our data indicate that PKCδ phosphorylates TAp63 proteins at Thr157 to stabilize them and promote cell apoptosis. Abstract : PKCδ can associate and up‐regulate TAp63 depending on PKCδ kinase activity. PKCδ up‐regulates TAp63 via increasing the protein stability of TAp63. Thr157 is critical for PKCδ‐mediated accumulation of TAp63. PKCδ up‐regulates TAp63‐mediated transactivation and cell apoptosis.